A constrained optimization model for partitioning students into cooperative learning groups - Heine, Matthew Alan, author; Kirby, Michael, advisor; Pinaud, Olivier, committee member; Henry, Kimberly, committee member (Colorado State University. Libraries, 2016)
The problem of the constrained partitioning of a set using quantitative relationships amongst the elements is considered. An approach based on constrained integer programming is proposed that permits a group objective function to be optimized subject to group quality constraints. A motivation for this problem is the partitioning of students, e.g., in middle school, into groups that target educational objectives. The method is compared to another grouping algorithm in the literature on a data set collected in the Poudre School District.